1998
DOI: 10.1152/ajpcell.1998.274.4.c892
|View full text |Cite
|
Sign up to set email alerts
|

Actions of substance P on membrane potential and ionic currents in guinea pig stellate ganglion neurons

Abstract: Neuropeptides are known to modulate the excitability of mammalian sympathetic neurons by their actions on various types of K+ and Ca2+ channels. We used whole cell patch-clamp recording methods to study the actions of substance P (SP) on dissociated adult guinea pig stellate ganglion (SG) neurons. Under current-clamp conditions, SG neurons exhibited overshooting action potentials followed by afterhyperpolarizations (AHP). The K+ channel blocker tetraethylammonium (1 mM), the Ca2+ channel blocker Cd2+ (0.1–0.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Successfully patched cells were held at Ϫ60 mV, a value of membrane potential near the reported resting membrane potential of guinea pig sympathetic neurons (13,24). Membrane currents were activated by 500-ms depolarizing voltage steps from the holding potential to 0 mV.…”
Section: Resultsmentioning
confidence: 99%
“…Successfully patched cells were held at Ϫ60 mV, a value of membrane potential near the reported resting membrane potential of guinea pig sympathetic neurons (13,24). Membrane currents were activated by 500-ms depolarizing voltage steps from the holding potential to 0 mV.…”
Section: Resultsmentioning
confidence: 99%
“…Can the inhibitory effect of Sub P on T cell adhesion be explained, at least in part, by the blocking of Kv1.3 channels? To answer this question, we tested, by electrophysiological techniques, whether Sub P, in a similar manner to its primary action on neurons 27, reduces the T cell membrane voltage-dependent [K + ] conductance. Whole-cell membrane currents were recorded from normal human T cells, in the presence of Sub P, using the voltage-clamp technique 17.…”
Section: Resultsmentioning
confidence: 99%
“…Although SP has been reported to directly modify other membrane conductances in mammalian autonomic neurons, such as inhibiting N-type Ca 2ϩ channel currents in rat sympathetic neurons (Shapiro and Hille 1993) and decreasing K ϩ permeability in neonatal rat sympathetic neurons (Dun and Mo 1988) and adult guinea pig celiac (Vanner et al 1993) and stellate ganglion neurons (Gilbert et al 1998), such effects of SP were not observed in rat parasympathetic intracardiac neurons. SP also failed to alter muscarinic ACh-sensitive K ϩ currents, in contrast to findings in frog sympathetic neurons where SP inhibits the M-current (see Brown 1988) and did not activate a nonspecific cation conductance as has been reported in guinea pig intracardiac ganglion neurons (Hardwick et al 1997).…”
Section: Discussionmentioning
confidence: 96%